STRATEGY OF DEVELOPING TOURISM BEACH (CASE STUDY: LAGUNA BEACH, KAUR REGENCY) - Mimi Kurnia Nengsih; Ida Ayu Made Er Meytha Gayatri (JELAJAH: Journal of Tourism and Hospitality, 2020)
Kaur District has desperately attractive potential beach tourism and also has the opportunity to bring local and foreign tourists and increase the locally-generated revenue. This potential tourism is the Laguna Beach. The objective of study was to determine the SWOT analysis that is implemented to develop strategy of Laguna Beach tourism in Kaur District. The data were collected by distributing questionnaires to respondents. The analytical method used is SWOT analysis to determine the internal factors (strength and weakness) and external factors (opportunity and threat), which will be incorporated into the SWOT matrix. The results of study showed the analysis of internal and external factors. The internal factor was strength with a total score of 22.2 and weakness with a total score of 3.7 so the internal factors achieved the value of 18.5. For the external factors, the opportunity had a total score of 16.96 while the threat had a total score of 8.41 so the external factors achieved the value of 8.55. According to SWOT diagram analysis, the marketing strategy of Laguna Beach in Kaur District can be placed in Quadrant I. This is shown by SO strategy in SWOT matrix that is Aggressive Strategy. This strategy can develop Laguna Beach because it has opportunity and strength in the future, thus it can increase the number of visitors/tourists at Laguna Beach.